OSCE Insights 2021 : Identifying Common Ground - Institute for Peace Research and Security Policy at the University of Hamburg / IFSH; Institute for Peace Research and Security Policy at the University of Hamburg / IFSH (Baden-Baden Nomos Verlagsgesellschaft mbH & Co. KG)
The 2021 edition of OSCE Insights discusses the possibility of compromise among the 57 participating states of the OSCE. It includes a special issue that compares the interests of selected participating States in the OSCE and offers recommendations for bridging divisions within the organization.
English
Keywords: GTB